2011
DOI: 10.5194/bg-8-2107-2011
|View full text |Cite
|
Sign up to set email alerts
|

Dust deposition: iron source or sink? A case study

Abstract: Abstract. A significant decrease of dissolved iron (DFe) concentration has been observed after dust addition into mesocosms during the DUst experiment in a low Nutrient low chlorophyll Ecosystem (DUNE), carried out in the summer of 2008. Due to low biological productivity at the experiment site, biological consumption of iron can not explain the magnitude of DFe decrease. To understand processes regulating the observed DFe variation, we simulated the experiment using a one-dimensional model of the Fe biogeoche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 60 publications
3
45
0
Order By: Relevance
“…Sedimentation, including carbon export, can be quantified and this represents a major step forward of that methodology affected by the dust input to the surface seawater, as a dissolved iron (DFe) scavenging was observed rapidly after the seeding, withdrawing almost 1 nM DFe from the whole water column inside the three mesocosms amended with dust while the atmospheric particles are settling . Those results were satisfactorily simulated with a one-dimensional model of the Fe biogeochemical cycle, coupled with a simple ecosystem model (Ye et al 2011). When a second dust wet deposition was simulated, iron dissolution from the dust particles was then evidenced due to the excess Fe binding ligand concentrations produced by the enhanced biological activity (Wuttig et al 2013).…”
Section: Experimental: In Situ Mesocosmsmentioning
confidence: 86%
See 2 more Smart Citations
“…Sedimentation, including carbon export, can be quantified and this represents a major step forward of that methodology affected by the dust input to the surface seawater, as a dissolved iron (DFe) scavenging was observed rapidly after the seeding, withdrawing almost 1 nM DFe from the whole water column inside the three mesocosms amended with dust while the atmospheric particles are settling . Those results were satisfactorily simulated with a one-dimensional model of the Fe biogeochemical cycle, coupled with a simple ecosystem model (Ye et al 2011). When a second dust wet deposition was simulated, iron dissolution from the dust particles was then evidenced due to the excess Fe binding ligand concentrations produced by the enhanced biological activity (Wuttig et al 2013).…”
Section: Experimental: In Situ Mesocosmsmentioning
confidence: 86%
“…Complex iron chemistry in the ocean (Tagliabue et al 2009), adsorptive scavenging of dissolved iron and solubilisation of particulate iron (Ye et al 2011), varying iron content of dust particles as well as varying iron solubility in seawater ) have been investigated in individual modelling studies but an explicit representation of these processes is still lacking in most of the biogeochemical models that do include an explicit representation of the iron cycle. In addition, Krishnamurthy et al (2009) have shown that increasing iron deposition could not only lead to increasing marine productivity in HNLC regions, but also significantly enhance N-fixation in subtropical regions if iron limitation of N-fixation is included.…”
Section: Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…(84). Model estimates (Ye et al, 2011) suggest a different affinity for these particles compared to biogenic particles, which justifies the split between biogenic and lithogenic materials in Eq. (50).…”
Section: Iron In Particlesmentioning
confidence: 99%
“…Thus, they may be transferred to the particulate pool, and settle to the ocean floor. Very few models have incorporated this potential important sink of dissolved iron (Ye et al, 2009(Ye et al, , 2011. In PISCES, we model this process following the approach chosen for DOM (see Sect.…”
Section: Ironmentioning
confidence: 99%